Pemanfaatan Media Business Model Canvas (BMC) Dalam Meningkatkan Hasil Belajar Perencanaan Usaha Pada Mata Kuliah Kewirausahaan - Dahmiri, Dahmiri; Setiawan, Wahyu Juari (Indonesian Educational Administration and Leadership Journal (IDEAL), 2023)
The learning outcomes of each student tend to vary according to their level of intellectual intelligence. Some students have a level of ability above other students, some are at an average level of ability and some are below the ability of other students. This can be seen when the teaching and learning process occurs, often some students dominate the atmosphere and others are just passive. In entrepreneurship courses, especially in discussions about business plans, students are often found to be passive, less creative, lacking ideas and just keep quiet. Therefore, in improving learning outcomes in Entrepreneurship courses, especially on the subject of business planning, one method that can be used is to use learning tools or media in the form of the Business Model Canvas (BMC). By using this media, it is hoped that student activity, creativity and learning outcomes will increase. The use of the Business Model Canvas (BMC) can stimulate student activity and creativity in the teaching and learning process because they are challenged to express their business ideas on the 9 canvas blocks that are available. Using this media will also be fun, discussing with each other, looking for new sources of knowledge and ultimately it is hoped that there will be an increase in learning outcomes. The results of the research concluded that the use of Business Model Canvas (BMC) media in the Entrepreneurship learning of the FEB Jambi University Management Study Program could be a solution in overcoming students' lack of activity in learning and minimal use of learning methods and media. Media Business Model Canvas (BMC) in Entrepreneurship learning in making business plans can improve student learning outcomes. The use of Business Model Canvas (BMC) media in Entrepreneurship learning can reduce verbalism in learning so that learning is more interesting, fun and not boring. Â